2019
DOI: 10.1103/physrevapplied.12.024052
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Computing on Spin-Torque Oscillator Array

Abstract: We numerically study reservoir computing on a spin-torque oscillator (STO) array, describing magnetization dynamics of the STO array by a nonlinear oscillator model. The STOs exhibit synchronized oscillation due to coupling by magnetic dipolar fields. We show that the reservoir computing can be performed by using the synchronized oscillation state. Its performance can be improved by increasing the number of the STOs. The performance becomes the highest at the boundary between the synchronized and disordered st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 46 publications
3
80
0
Order By: Relevance
“…In particular, many studies have already been conducted on spin-torque nano-oscillators with experimental results [10,11,[13][14][15][16] demonstrating promising performance as RC implementations. Further simulations [17,18] indicate the potential for improved performance by using arrays of coupled oscillators. Other proposed spintronic implementations are systems utilising magnetic skyrmion memristors [19] and spin-wave (SW) interference in garnet films [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, many studies have already been conducted on spin-torque nano-oscillators with experimental results [10,11,[13][14][15][16] demonstrating promising performance as RC implementations. Further simulations [17,18] indicate the potential for improved performance by using arrays of coupled oscillators. Other proposed spintronic implementations are systems utilising magnetic skyrmion memristors [19] and spin-wave (SW) interference in garnet films [12].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies [394], [395], [396], [397], [386] have revealed that reservoir computing can also be performed based on mutually coupled magnonic oscillators using synchronization effects. Synchronization is the fundamental nonlinear effect [398] that can drive the magnonic oscillator network to a collective state, where the phases and frequencies of oscillators are equal or may differ by a constant.…”
Section: Magnonic Neuromorphic Computingmentioning
confidence: 99%
“…Many currently discussed assets of physical reservoirs can be understood from this perspective. In particular, spintronics devices have been gaining attention as an appropriate substrate for PRC because of their compactness, high-speed processing, and energy efficiency while being able to function at normal temperatures [73][74][75][76][78][79][80][81][82][83][84][85]. These assets are somewhat common in the computer science field, but spintronics devices also contain an inter- esting additional property: they show high durability in radioactive environments [183] (Fig.…”
Section: Exploiting Physical Dynamics For Computational Purposesmentioning
confidence: 99%